Microbiome, Transcriptome, and Metabolomic Analyses Revealed the Mechanism of Immune Response to Diarrhea in Rabbits Fed Antibiotic-Free Diets - Wang, Jie; Fan, Huimei; Xia, Siqi; Shao, Jiahao; Tang, Tao; Chen, Li; Bai, Xue; Sun, Wenqiang; Jia, Xianbo; Chen, Shiyi; Lai, Songjia (Frontiers in Microbiology, 2022)
In the production of rabbits, the diarrhea of rabbits was induced by feeding antibiotic-free feed. The gut is an important defense against the body's barriers, of which the duodenum is important parts to help digest food and absorb nutrients. However, the mechanisms underlying the roles of the gut microbiome and fecal metabolome in rabbit diarrhea caused by feeding antibiotic-free diet have not been characterized. Recently, only a single study has been conducted. To further characterize antibiotic-free feed feed additives caused diarrhea in weaned rabbits, we combined multi-omics techniques, including 16S rRNA sequencing, transcriptome sequencing, and LC/MS analysis, to analyzed gut microbial compositions and functions, and further characterize fecal metabolomic profiles in diarrhea rabbit caused by by feeding antibiotic-free feed. The results showed that the duodenal tissue of diarrhea rabbits was diseased, the compsition of intestinal microbe was significantly changed, the diversity of intestinal microbe was decreased, and the distribution of intestinal microbe group was changed. Functional analysis based on the cluster of GO and KEGG annotations suggested that 2 functional GO categories belonged to the metabolism cluster and 5 KEGG pathways related to metabolic pathways were significantly enriched in diarrhea rabbit. Moreover, real-time quantitative PCR (RT-qRCR) was used to verify the significant expression of genes related to diarrhea. Metabolomics profiling identified 432 significantly differently abundant metabolites in diarrhea rabbit, including amino acids and amino acid derivatives.. These amino acids were enriched in the tryptophan metabolic pathway. Moreover, functional correlation analysis showed that some altered gut microbiota families, such as Parasutterella, significantly correlated with alterations in fecal metabolites. Collectively, the results suggested that an altered gut microbiota is associated with antibiotic-free feed additives caused diarrhea in weaned rabbit pathogenesis.